Empirical Investigation of the Relationship among Profitability, Market Structure and Efficiency in Indian Banking Sector - Tang, Sirui (2015)
After the employment of several reforms that happened mainly in 1990s, the face of the Indian banking sector has been impressively changed. The purpose of these policies, such as deregulation and lowering entry barriers, was to enhance the efficiency, flexibility and the level of competition in the Indian banking sectors. Therefore, this study aims to figure out what is the relationship among market structure, efficiency and profitability in Indian banking sector from 2009 to 2014, after the reforms in 1990s. Four hypotheses – Structure-Conduct Performance (SCP) hypothesis, Relative Market Power (RMP) hypothesis, X-efficiency (ESX) hypothesis, and the Scale-efficiency (ESS) hypothesis, are tested by using panel data regression. Moreover, the necessary condition for efficient structure hypotheses and the ‘quiet life’ hypothesis are further tested. Estimation of these models shows some supports for the SCP hypothesis during the researched period. The X-efficiency hypothesis is preliminarily supported, but there is no evidence to support the necessary condition. Thus for the Indian banking sector, high profits could obtained from the higher level of market concentration. Overall, the stronger role of competition policy might be suggested for the Indian government to better development of its banking industry.